CAREER COUNSELING GROUP SUPERVISION: A New Approach in Master's Level Counseling Programs. - Lara Hilton, Tracy M.; Brant, Jamie; Vess, Logan (Career Planning & Adult Development Journal)
The article discusses the main goals of counselor trainee supervision during the university training experience. It explores the need to protect the welfare of clients as the most significant goal and foster supervisee agency in areas of self-esteem, counseling knowledge and counseling skills. It highlights the rationale for the theoretical based of supervisee-centered outsider-witnessing career group supervision (SCOWCGS).